Dekomposisi Petani dan Struktur Kerja dalam Masyarakat Pertanian - Elanda, Yelly; Santoso, Budhy; Yuswadi, Hary (Laboratorium Sosiologi FISIP Universitas Jember, 2013)
The existence of the orange plantation at Gadingrejo Village, Umbulsari District, Jember Regency has attracted all the capitalist to do an investment. Usually, they’re doing investment to do the rented land and to sell their crops to the middlemen or wholesalers. Because currently, the market for direct agriculture is done on the agricultural land which is through the land rent. The land rent system which is an investment form of all the capitalist has created a new position on the land rent system and that is a broker and the confidant. The presence of both local & foreign tenant has created capital decomposition which later would also be followed by the manpower decomposition. Actually, in Gadingrejo Village, the possibilities of the occurrence of the manpower decomposition have been found. And there were 17 possibilities of it. These condition that the Gadingrejo Village peoples called welfare. And these conditions were different from Scott’s research condition, where Scott saw the deterioration of the farmer caused by the presence of the capitalist. And because of that, as the results the manpower got decreased, it creates unemployment and also there were three kinds of land tenant positions. Keywords: decomposition of capital, decomposition of manpower, decomposition of the farmer and land rental